Pemberian Nafkah Pasca Cerai Kepada Mantan Istri Pegawai Negeri Sipil Dalam Peraturan Pemerintah Nomor 45 Tahun 1990 Perspektif Maslahah - Mohammad Fahmi Fahriza; Ahmad Mustafid; Umniatul Aula; Dhea Rizky Anggraini Setyati Ningrum; Tri Maita Widasari; Shafa Fadia Madjid; Windiani Purwaningrum (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Government Regulation No. 10 of 1983 jo. Government Regulation No. 45 of 1990 states in article 8, if there is a divorce at the will of a male civil servant, he must give up part of his salary for the livelihood of his wife and children. In fact, the obligation to guarantee the needs of a wife's life is as long as the marriage still exists and until the iddah period of the ex-wife if divorced. The purpose of this study is to analyze the provision of providing income to ex-wives among civil servants. The type of research used is qualitative research based on the sources of the Marriage Law and government regulations with descriptive analysis methods. The concept of benefit is not necessarily achieved with the rules for post-divorce salary distribution. This can be seen in the decision of the Supreme Court of the Republic of Indonesia Number 02 P/HUM/2017 in which there is a dissenting opinion by the chief judge that the ex-husband with the status of a State Civil Apparatus (ASN) has no obligation to give a share of his salary to his ex-wife. Likewise, the ex-wife does not have the right to get a share of her ex-husband's salary because there is no marital bond between the two of them.